Generation of ionic liquid tolerant Pseudomonas putida KT2440 strains via adaptive laboratory evolution. Issue 17 (10th August 2020) - Lim, Hyun Gyu; Fong, Bonnie; Alarcon, Geovanni; Magurudeniya, Harsha D.; Eng, Thomas; Szubin, Richard; Olson, Connor A.; Palsson, Bernhard O.; Gladden, John M.; Simmons, Blake A.; Mukhopadhyay, Aindrila; Singer, Steven W.; et al.
Abstract : Pseudomonas putida KT2440, a promising microbial platform for industrial biotechnology was tolerized to low-cost biomass decomposing ionic liquids via the adaptive laboratory evolution. Abstract : Although the use of ionic liquids (ILs) for the pretreatment of lignocellulosic biomass has been limited due to high costs, recent efforts to develop low-cost protic ILs show promise for achieving cost-effectiveness for biorefineries. However, an additional challenge remains in that ILs present in biomass hydrolysates are toxic to most microbial hosts, resulting in poor growth phenotypes. To address this issue, we applied an adaptive laboratory evolution (ALE) approach for tolerizing Pseudomonas putida KT2440, an industrially relevant bacterial host, to two low-cost ILs (triethanolammonium acetate [TEOH][OAc] and triethylammonium hydrogen sulfate [TEA][HS]). After continuous cultivations with gradually increased IL levels, we obtained evolved strains showing significant improvements in their growth performance under high concentrations of the ILs (maximum 4% [TEOH][OAc] and 8% [TEA][HS], in w/v) at which the wild-type strain cannot grow. Sequencing of evolved strains revealed multiple regions where mutations were associated with improved performance in minimal media conditions ( relA, gacS, oprB /PP_1446, fleQ, tktA, and uvrY /PP_4100) and in IL-specific conditions (PP_5350, PP_4929/ emrE, oprD, and PP_5324). We further validated the causality of the PP_5350 and emrE genes for improved IL tolerance via reverse engineering and transcriptomic analysis. A common mutation in the PP_5350 gene, encoding a RpiR family transcriptional regulator, was shown to significantly upregulate the glyoxylate cycle for efficient acetate catabolism. In addition, it was suggested that the emrE gene encodes an efflux pump which can export [TEA][HS]. Finally, the cultivation of two of the best performing evolved strains with IL-treated biomass hydrolysates demonstrated their considerable potential to be used as platform strains. Taken as a whole, this work provides strains for utilization of IL-treated biomass and a mechanistic understanding that could be further leveraged to develop efficient microbial bioprocesses.